Global temperature, R&D expenditure, and growth - Michael Donadelli; Patrick Grüning; Marcus Jüppner; Renatas Kizys (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
We shed new light on the macroeconomic effects of rising temperatures. In the data, a shock to global temperature dampens expenditures in research and development (R&D). We rationalize this empirical evidence within a stochastic endogenous growth model, featuring temperature risk and growth sustained through innovations. In line with the novel evidence in the data, temperature shocks undermine economic growth via a drop in R&D. Moreover, in our endogenous growth setting temperature risk generates non-negligible welfare costs (i.e., 11% of lifetime utility). An active government, which is committed to a zero fiscal deficit policy, can offset the welfare costs of global temperature risk by subsidizing the aggregate capital investment with one-fifth of total public spending.
urn:nbn:de:hebis:30:3-451934
Keywords: E30; G12; Q00; 330; Global Temperature; R&D; Welfare Costs